STUDI PENCAMPURAN SERAT ENCENG GONDOK PADA CAMPURAN BETON DENGAN PENGGUNAAN AGREGAT KASAR DARI KECAMATAN MANTUP - Kartisyah Wulandari; Dwi Kartikasari (U Karst, 2019)
The purpose of this study is to know the characteristics of the coarse aggregate of Mantup and to determine the effect of natural water hyacinth fiber addition from the use of the coarse aggregate of Mantup towards the concrete compressive strength. This research method employs experimental methods with mix design (reference of SNI 03-2834-2000). To determine the effect of adding the natural water hyacinth fiber and coarse aggregate of Mantup, the experiment is done with the variation of 0%, 4%, 6%, and 8% by weight of the cement. The test object used is cylinders Ø15 cm × 30 cm. The number of samples made as many as 12 samples, consisting of 4 variations and for each variation is made 3 samples. After doing the immersion for 7 days, it is done the testing that can be conversed to 28 days. From the test, obtained the result that the compressive strength for the 0% fiber variation produces compressive strength of 94,36kg/cm², for 4% fiber variation produces compressive strength of 40.44 kg/cm², for 6% fiber variation produces compressive strength of 48.53 kg/cm², and for the 8% fiber variation produces compressive strength of 47.18 kg/cm². Keywords :Water Hyacinth; Coarse Aggregate of Mantup; Compressive Strength of ConcreteTujuan dari penelitian ini adalah untuk mengetahui karakteristik agregat kasar Mantup dan untuk mengetahui pengaruh penambahan serat eceng gondok dari penggunaan agregat kasar Mantup terhadap kekuatan tekan beton. Metode penelitian ini menggunakan metode eksperimental dengan desain campuran (mengacu pada SNI 03-2834-2000). Untuk mengetahui pengaruh penambahan serat eceng gondok air dan agregat kasar Mantup, percobaan dilakukan dengan variasi 0%, 4%, 6%, dan 8% berat semen. Objek uji yang digunakan adalah silinder Ø15 cm × 30 cm. Jumlah sampel yang dibuat sebanyak 12 sampel, terdiri dari 4 variasi dan untuk setiap variasi dibuat 3 sampel. Setelah melakukan perendaman selama 7 hari, dilakukan pengujian yang dapat dikonversi menjadi 28 hari. Dari pengujian, diperoleh hasil bahwa kuat tekan untuk variasi serat 0% menghasilkan kuat tekan 94,36kg / cm², untuk variasi serat 4% menghasilkan kuat tekan 40,44 kg / cm², untuk variasi serat 6% menghasilkan kuat tekan 48,53 kg / cm², dan untuk variasi serat 8% menghasilkan kuat tekan 47,18 kg / cm².Kata Kunci: Eceng Gondok Air; Agregat Kasar Mantup; Kekuatan Beton Tekan